Regulatory requirements for nuclear power plant site selection in Malaysia—a review. (15th September 2016) - Basri, N A; Hashim, S; Ramli, A T; Bradley, D A; Hamzah, K
Abstract: Malaysia has initiated a range of pre-project activities in preparation for its planned nuclear power programme. Clearly one of the first steps is the selection of sites that are deemed suitable for the construction and operation of a nuclear power plant. Here we outline the Malaysian regulatory requirements for nuclear power plant site selection, emphasizing details of the selection procedures and site characteristics needed, with a clear focus on radiation safety and radiation protection in respect of the site surroundings. The Malaysia Atomic Energy Licensing Board (AELB) site selection guidelines are in accord with those provided in International Atomic Energy Agency (IAEA) and United Stated Nuclear Regulatory Commission (USNRC) documents. To enhance the suitability criteria during selection, as well as to assist in the final decision making process, possible assessments using the site selection characteristics and information are proposed.